2018
DOI: 10.3892/ol.2018.9879
|View full text |Cite
|
Sign up to set email alerts
|

Effect on macrophage proliferation of a novel polysaccharide from Lactarius deliciosus (L. ex Fr.) Gray

Abstract: The fundamental mechanisms underlying the preventional and therapeutic effects of polysaccharides from fungi, including the immunostimulatory, antiviral and antitumor effects, are considered to occur through the modulation and stimulation of the macrophage and complement system. LDG-A, a novel polysaccharide from Lactarius deliciosus (L. ex Fr.) Gray exhibits marked antitumor activities in vivo. However, the underlying molecular mechanism of the antitumor activities of LDG-A remains unclear. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A). Growing evidence shows that natural polysaccharides promote cell proliferation, such as the polysaccharides from Lactarius deliciosus and Fructus Mori . The toxicity of 5‐FU against the cancer cell lines was significant, causing over 50% of cell death (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A). Growing evidence shows that natural polysaccharides promote cell proliferation, such as the polysaccharides from Lactarius deliciosus and Fructus Mori . The toxicity of 5‐FU against the cancer cell lines was significant, causing over 50% of cell death (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lactarius deliciosus Gray is a rare edible mushroom with high nutritional value that has attracted increasing attention (7). As one of the main effective components of L. deliciosus, its polysaccharides exhibit a broad spectrum of application, including anti-tumor activity, macrophage immunostimulant activity and B cell immunostimulant activity (8)(9)(10)(11). Therefore, studies on the structure and biological activity of L. deliciosus polysaccharide are of great significance for the application and development of L. deliciosus treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies on the structure and biological activity of L. deliciosus polysaccharide are of great significance for the application and development of L. deliciosus treatment. In previous studies, certain water-soluble polysaccharides have been extracted and purified from the fruiting bodies of wild L. deliciosus (8)(9)(10). These studies also revealed that L. deliciosus polysaccharides exhibit immunoregulatory and anti-tumor activities (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-320 regulates the mouse GC proliferation and steroid production by targeting E2F1 and SF-1 in the follicular development (Yin et al, 2014). E2F transcription factors play a key role in promoting advancement of the cell division cycle from the G1 to S phases (Shauna & Frederick 2012). Therefore, E2F1 might regulate the ovarian GC growth and then play a role in follicular development.…”
mentioning
confidence: 99%